2015
DOI: 10.1371/journal.pone.0144843
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual Risk Behaviours and Willingness to Be Circumcised among Uncircumcised Adult Men in Uganda

Abstract: BackgroundThere has been substantial demand for safe male circumcision (SMC) in Uganda in the early programme scale-up phase. Research indicates that early adopters of new interventions often differ from later adopters in relation to a range of behaviours. However, there is limited knowledge about the risk profile of men who were willing to be circumcised at the time of launching the SMC programme, i.e., potential early adopters, compared to those who were reluctant. The aim of this study was to address this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
3
15
1
Order By: Relevance
“…Instead, subsequent sexual risk behaviors could be driven by other factors such as already prevailing behavior, residence in a fishing community, and low exposure to targeted messaging, as shown in Supplemental Table 1 and Supplemental Table 2. Our findings are also in contrast with some other studies in Uganda 10,11 and other settings 13,23 that found an association. Although one of these studies explicitly reported that circumcised men had higher prevalence of sexual risk behaviors, they observed that majority of these men were HIV negative.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Instead, subsequent sexual risk behaviors could be driven by other factors such as already prevailing behavior, residence in a fishing community, and low exposure to targeted messaging, as shown in Supplemental Table 1 and Supplemental Table 2. Our findings are also in contrast with some other studies in Uganda 10,11 and other settings 13,23 that found an association. Although one of these studies explicitly reported that circumcised men had higher prevalence of sexual risk behaviors, they observed that majority of these men were HIV negative.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to findings in a cross-sectional study from the 2011 Uganda AIDS Indicator Survey by Kibira et al which suggested that early adopters of circumcision probably did so because they were already engaging in some sexual risk behaviors. 23 Due to this concern, we controlled for baseline sexual risk behavior in the final models although we had found no association with exposure status (circumcision or uncircumcised). It is important to note that that particular study considered perceived risk for HIV but not the actual HIV status of men.…”
Section: Discussionmentioning
confidence: 99%
“…Circumcision prevalence among men 15 to 49 years in Uganda was 27% in 2011 [17], but with high levels of willingness to be circumcised among uncircumcised men [18]. Those who expressed willingness at the time also seemed to be the ones with the largest need for protective measures [18].…”
Section: Introductionmentioning
confidence: 99%
“…Those who expressed willingness at the time also seemed to be the ones with the largest need for protective measures [18]. SMC has since been promoted using mass media, posters, billboards, and automobiles with loudspeakers that drive through communities, especially when outreach services are planned.…”
Section: Introductionmentioning
confidence: 99%
“…(Table 7) On transactional sex, age, marital status, location and occupation were significantly associated with engaging in transaction sex. The odds of being involved in transactional sex among those aged [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] was 81% less compared to those aged 18-29 (OR 0.19, 95% CI 0.09, 0.37 p <0.0001). The odds of being involved in transaction sex among the married ones was 88% less compared to those that were single (OR 0.12, 95% CI 0.07, 0.22 p <0.0001).…”
Section: Univariate and Multivariate Analysis On Sexual Practicesmentioning
confidence: 99%